2021
DOI: 10.1051/smdo/2021012
|View full text |Cite
|
Sign up to set email alerts
|

Design and simulation of multilayer hybrid foam material for acoustic application

Abstract: New acoustic multilayer absorber fabricated by coupling closed-cell metallic foam and open-cell polymeric foam, which aimed to develop a practical use of metallic foam in the noise control application. In prior, the individual sound absorption coefficient of both foam materials with different thicknesses measured by the impedance tube method as per ASTM E-1050. Using inverse characterization technique, the intrinsic properties needed for five parameter models in a numerical study are predicted. The measured ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…[41] Advanced research revealed numerous advantages of homo copolymer-based surfactants over other types, few of them are their cost-effectiveness and viable characterization. [42] Few such types have reported to be exploited as PMS in emulsion polymerizations. [43,44] Though, few random copolymers were also reported to have limitations because of their functional group adherence on to the particle surface that reduce their efficacy to be used in applications as paints, coatings, finishes, or polishes.…”
Section: Random Copolymersmentioning
confidence: 99%
“…[41] Advanced research revealed numerous advantages of homo copolymer-based surfactants over other types, few of them are their cost-effectiveness and viable characterization. [42] Few such types have reported to be exploited as PMS in emulsion polymerizations. [43,44] Though, few random copolymers were also reported to have limitations because of their functional group adherence on to the particle surface that reduce their efficacy to be used in applications as paints, coatings, finishes, or polishes.…”
Section: Random Copolymersmentioning
confidence: 99%
“…[44] The non-acoustic parameters required for simulating flow resistivity, tortuosity, porosity, VSL, and TCL are obtained by inverse characteristics or by physical experiments. [45][46][47] The novelty of this study focuses on manufacturing biobased PU composite foam using the AHR technique, which is employed in various applications, including regulating equipment noise, automobiles, and aircraft. The impact of the wt% PVDF, MgO, and Ni on sound absorption and noise reduction coefficient are being evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…[ 44 ] The non‐acoustic parameters required for simulating flow resistivity, tortuosity, porosity, VSL, and TCL are obtained by inverse characteristics or by physical experiments. [ 45–47 ]…”
Section: Introductionmentioning
confidence: 99%